Protective Effect of Murraya koenigii Against D-Galactose-Induced Cognitive Dysfunction in Swiss Albino Mice - Rathi, Anjul; Singh, Lubhan (International Journal of Aquatic Research and Environmental Studies, 2026)
Alzheimer's disease (AD) and age-associated cognitive deficits are primary neurodegenerative diseases and are commonly related to progressive impairment in memory, oxidative stress, neuro inflammation, and neuronal loss. Chronic D galactose administration has been widely utilized in experimental animals to induce aging-associated deficits and cognitive decline; it has been known to induce oxidative damage and trigger inflammatory reactions in an aged brain. Natural products that are rich in antioxidant and anti-inflammatory properties are being explored extensively for the potential therapy of neurodegenerative diseases.  The main goal of this investigation was to evaluate the neuroprotective efficacy of Murraya koenigii extract in the case of D-galactose-induced cognitive deficits in Swiss albino mice. The Swiss albino mice were separated into five groups, i.e., Group I- Normal Control, Group II- Murraya koenigii extract 500 mg/kg Per se, Group III- D-galactose (1000mg/kg, s.c.) + Group IV- Murraya koenigii extract 250mg/kg + D-galactose (1000mg/kg, s.c.), Group V- Murraya koenigii extract 500mg/kg + D-galactose (1000mg/kg, s.c.). The cognitive functions of Swiss albino mice were assessed by the use of the Morris Water Maze, Passive Avoidance Test, and Open Field Test. The levels of antioxidant and pro-oxidant parameters, namely the concentrations of MDA, SOD, reduced GSH, and CAT in the cerebral cortex of animals, were quantified.  The levels of AChE activity and the cytokines that promote inflammation, namely TNF-α, IL-1α, and IL-10, were also quantified. Brain tissues were prepared and stained with H&E for histopathological studies. The outcome suggests that treatment with Murraya koenigii may lead to the recovery of cognitive impairment by enhancing antioxidant, anti-inflammatory, and cholinergic actions to provide neuroprotection against D-galactose mediated neurodegeneration. This study may demonstrate the plant's potential as a therapeutic remedy for age-associated cognitive disorders and Alzheimer's disease.
Keywords: Murraya koenigii, D-galactose, Cognitive Dysfunction, Alzheimer's Disease, Neuroprotection.